Study on Low Temperature Applications of R404A for Semi-hermetic Reciprocating Refrigeration Compressor - Qin Haijie; Yu Shitao; Liu Jinglin (Zhileng xuebao)
Experiments on a reciprocating compressor C- L150M82 using R404A and R22 were conducted under low temperature working conditions. The feasibility of replacing R22 with R404A was analyzed based on the experimental data. The results show that with the same configuration and under the low temperature working condition, the refrigerating capacity of the compressor with R404A is greatly higher than that with R22, if the condensing temperature does not change. With the falling of evaporating temperature, the capacity can rise by 10% - 30%. Moreover, at the same condensing temperature, the evaporating temperature for the compressor using R404A can reach - 45%. Furthermore, the discharge temperature of the compressor using R404A is lower than that using R22 significantly. In addition, the application of both superheat and subcool recycles can improve the performance of R404A refrigeration system.